Maghrebians (or Mauri) speak Magharibi, not Arabic - Abdou Elimam (Insights into Language, Culture and Communication, 2023)
After defeating and pushing aside the Carthaginians, the Romans named the territory of north Africa Mauretania and its population, Mauri. Later on, historians have had to reflect on the origin of the term mauri to designate the population or Mauretania to name the territory. Besides the signification of the Latin/Greek word « mauri » which means « black », it is admitted, as well, that the word Mauri is a transcription, into the Latin alphabet, of a punic word meaning « the west » or « the westerners ». If the latter meaning is 2000 years old, the other approbation is relatively modern and suspected of ideological biases. The punic word maġaribis, transcribed mauri/ma’ari/mahauri, really makes sense since it means the west in Punic - the 15 century-long North African lingua franca. Received: 11 February 2023 Accepted: 21 February 2023 Published: 20 March 2023